BOOK REVIEW: THE VALUE OF QUESTIONS IN LET’S TALK TEXTBOOK PUBLISHED BY PAKAR RAYA FOR THE SECOND YEAR STUDENTS OF JUNIOR HIGH SCHOOL AT SLTP N SIAK HULU - Destri Wahyuningsih (English Study Program University of Pasir Pengaraian, 2017)
This research is a book review of questions in